2002
DOI: 10.1111/j.1348-0421.2002.tb02768.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐Stranded nef RNA Interferes with Human Immunodeficiency Virus Type 1 Replication

Abstract: RNA interference (RNAi) has been reported to be post‐transcriptional gene silencing (PTGS) by approximately 500 nucleotide‐(nt)‐long double‐stranded (ds) RNA that specifically targets homologous sequences of messenger RNA. In this report, we describe inhibition of HIV‐1 transcription by synthetic dsRNAs constructed with mutated nef genes (nef dsRNAs) derived from long‐term non‐progressors (LTNPs) using cotransfection of the target gene‐expressing plasmid and dsRNA. The effects of nef dsRNAs were examined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…42,43 In vitro made long dsRNAs have been used to inhibit HIV-1 production under certain conditions without induction of the IFN response. 16,24 We have previously demonstrated potent inhibition of HIV-1 replication in T cells that stably express an shRNA targeted to viral nef gene sequences. 19 To test whether endogenously expressed lhRNA and long dsRNA can inhibit HIV-1 at least as potently as sh-nef, we constructed and tested a series of DNA constructs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 In vitro made long dsRNAs have been used to inhibit HIV-1 production under certain conditions without induction of the IFN response. 16,24 We have previously demonstrated potent inhibition of HIV-1 replication in T cells that stably express an shRNA targeted to viral nef gene sequences. 19 To test whether endogenously expressed lhRNA and long dsRNA can inhibit HIV-1 at least as potently as sh-nef, we constructed and tested a series of DNA constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to reduce the chance of viral escape include the simultaneous use of multiple siRNAs 22,23 or the use of long-hairpin RNA (lhRNA, a single-hairpin molecule) or long dsRNA (two complementary molecules that form a duplex). 16,24 Another possibility is the use of miRNA-based approaches, which do not require perfect sequence complementarity. 25,26 Several reports describe efficient RNAi induction by lhRNA and long dsRNA as in vitro generated transcripts that are transfected into cells or as gene constructs that produce the transcripts intracellularly.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, several groups have shown that HIV-1-specific long hairpin (lhRNA) or long dsRNA endogenously expressed can inhibit HIV-1 replication without induction of IFN response [115][116][117][118]. More recently, Konstnatinova and coworkers reported a potent trans-inhibition of HIV replication using an HIV-1 variant with a 300pb-lhRNA at the 3 0 genome position of the nef gene [119].…”
Section: Rnai As a New Tool Against Hiv-1mentioning
confidence: 99%
“…Viral genes including tat, rev, nef, and gag have been silenced, resulting in successful inhibition of viral replication in cultured cells (64,(93)(94)(95)(96)(97)(98)(99). Cellular genes such as CD4, CCR5 and CXCR4 that are necessary for viral infection were also targeted giving similar results (99,100).…”
Section: Medical Applicationsmentioning
confidence: 99%